2014
DOI: 10.3171/2014.4.spine14269
|View full text |Cite
|
Sign up to set email alerts
|

Guideline update for the performance of fusion procedures for degenerative disease of the lumbar spine. Part 6: Discography for patient selection

Abstract: Identifying the etiology of pain for patients suffering from chronic low-back pain remains problematic. Noninvasive imaging modalities, used in isolation, have not consistently provided sufficient evidence to support performance of a lumbar fusion. Provocative testing has been used as an adjunct in this assessment, either alone or in combination with other modalities, to enhance the diagnostic capabilities when evaluating patients with low-back pain. There have been a limited number of studies investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
(11 reference statements)
0
20
0
1
Order By: Relevance
“…Although discography has the potential to assist in diagnosing disc derangement, consideration of the consistent reports of the high false-positive rates and new findings of accelerated degeneration in discs that undergo discography make it difficult to recommend the procedure for the diagnosis of discogenic back pain. There is evidence to suggest an association between advanced degenerative spondylosis and a history of undergoing provocative discography [2]. The validity of lumbar discography is very much in doubt, which is underscored by a more recent practice recommendation published by the American Pain Society, which suggested that provocative lumbar discography should not be used for making the diagnosis of a discogenic source of pain in the setting of low back pain [3].…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Although discography has the potential to assist in diagnosing disc derangement, consideration of the consistent reports of the high false-positive rates and new findings of accelerated degeneration in discs that undergo discography make it difficult to recommend the procedure for the diagnosis of discogenic back pain. There is evidence to suggest an association between advanced degenerative spondylosis and a history of undergoing provocative discography [2]. The validity of lumbar discography is very much in doubt, which is underscored by a more recent practice recommendation published by the American Pain Society, which suggested that provocative lumbar discography should not be used for making the diagnosis of a discogenic source of pain in the setting of low back pain [3].…”
Section: Dear Editormentioning
confidence: 99%
“…The validity of lumbar discography is very much in doubt, which is underscored by a more recent practice recommendation published by the American Pain Society, which suggested that provocative lumbar discography should not be used for making the diagnosis of a discogenic source of pain in the setting of low back pain [3]. The new guideline update for the performance of fusion procedures for degenerative disease of the lumbar spine showed that based primarily on retrospective studies, discography, as a standalone test, is not recommended to formulate treatment strategies for patients with low back pain [2]. However, we found the patients in this study were enrolled from June 2007 through November 2010.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…(See Willems et al, 2013;Chou et al, 2009;Eck, 2014. (See Willems et al, 2013;Chou et al, 2009;Eck, 2014.…”
Section: In This Issuementioning
confidence: 99%
“…Some reports have shown that disc degeneration was a source of LBP [4,5], whereas other reports have shown that there was no relationship between disc degeneration and LBP [6,7]. Reports have also shown that discogenic LBP associated with degenerative disc disease (DDD) is confirmed by the MRI findings and response to the injection of contrast media or local anesthesia into the disc [810]. Schwarzer et al reported that 39% of cases of chronic LBP are discogenic, and the diagnosis is made by computed tomography after discography [11].…”
Section: Introductionmentioning
confidence: 99%